2021
DOI: 10.57138/edqe3556
|View full text |Cite
|
Sign up to set email alerts
|

Employment and Unemployment amongst Educated Youth in Bangladesh: An Exploratory Analysis

Abstract: This is an exploratory exercise that attempts to identify the potential for carrying out online socio-economic surveys in Bangladesh, taking the question of “educated unemployment” as a test case. The topic is of great interest not just in Bangladesh but also throughout South Asia and beyond, where the issue is of particular concern in the context of rapid growth and rising aspirations amongst young people. Most studies depend either on own data generation or periodic national level surveys like the Labour For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…But, at the same time, huge number of university graduates remain in the unemployment pool for a long time. More than one-third of the youth are unemployed (Murshid, Mahmood & Shashi, 2019). In the face of fourth industrial revolution, industries need to constantly adjust their business model and production process.…”
Section: Introductionmentioning
confidence: 99%
“…But, at the same time, huge number of university graduates remain in the unemployment pool for a long time. More than one-third of the youth are unemployed (Murshid, Mahmood & Shashi, 2019). In the face of fourth industrial revolution, industries need to constantly adjust their business model and production process.…”
Section: Introductionmentioning
confidence: 99%
“…This huge amount of young population demonstrates an immense potentiality / opportunity as well as 'threat' for Bangladesh if proper development and opportunities are not given to them. Thus, "there is a growing concern in the country that if large numbers of educated, young people are bypassed by the development process and fail to obtain employment, this might lead to widespread social unrest and encourage extremism" (Murshid et al, 2019). It is pertinent to mention that almost half of the young are unemployed and 23% are illiterate (Muzahid, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is pertinent to mention that almost half of the young are unemployed and 23% are illiterate (Muzahid, 2015). In addition, educated unemployment is growing / increasing massively in Bangladesh (Murshid et al, 2019). As far as youth development index is concerned, Bangladesh performed the lowest among the commonwealth countries.…”
Section: Introductionmentioning
confidence: 99%
“…The Bangladesh Labor Force Survey 2016-17 reported the rate of unemployment amongst graduates as 11.2%, which is much higher than the national unemployment rate of 4.2% (Bangladesh Bureau of Statistics, 2018). Surprisingly, Murshid et al (2019) reported the graduate unemployment rate as 33.2% in Bangladesh. On the contrary, industries in Bangladesh run with 10-15% vacant positions every year owing to the lack of qualified hires (Nusrat and Sultana, 2019).…”
mentioning
confidence: 99%